Surgical Swab Counting: A Qualitative Analysis from the Perspective of the Scrub Nurse. Issue 5 (May 2014) - D'lima, D; Sacks, M; Blackman, W; Benn, J
The aim of the study was to conduct a qualitative exploration of the sociotechnical processes underlying retained surgical swabs, and to explore the fundamental reasons why the swab count procedure and related protocols fail in practice. Data was collected through a set of 27 semistructured qualitative interviews with scrub nurses from a large, multi-site teaching hospital. Interview transcripts were analysed using established constant comparative methods, moving between inductive and deductive reasoning. Key findings were associated with interprofessional perspectives, team processes and climate and responsibility for the swab count. The analysis of risk factors revealed that perceived social and interprofessional issues played a significant role in the reliability of measures to prevent retained swabs. This work highlights the human, psychological and organisational factors that impact upon the reliability of the process and gives rise to recommendations to address contextual factors and improve perioperative practice and training.